2022
DOI: 10.1021/acs.jpcc.2c04302
|View full text |Cite
|
Sign up to set email alerts
|

Nail-like α-SnWO4 Array Film with Increased Reactive Facets for Photoelectrochemical Water Splitting

Abstract: α-SnWO4 is a good candidate for photoelectrochemical (PEC) water splitting due to its suitable band position that straddles the H+/H2 and O2/H2O redox potentials. However, its poor charge transfer ability results in unsatisfactory PEC performance. From the view of material design, a nail-like α-SnWO4 array film was constructed by a hydrothermal method assisted by halogen ions, and the corresponding physical and PEC properties are discussed. Density functional theory (DFT) calculations were also performed to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…A slightly different hydrothermal synthesis process was reported by Liu et al , who successfully synthesized nail-like α-SnWO 4 nanorod arrays on WO 3 films. 58 In contrast to the hydrothermal conversion involving pre-existing nanostructured WO 3 films, this approach utilized dense WO 3 films as starting points, and the hydrothermal step simultaneously converted WO 3 to α-SnWO 4 and promoted the growth of α-SnWO 4 nanorods. The hydrothermal synthesis was performed in an aqueous solution containing SnCl·2H 2 O, NaF, and N 2 H 4 .…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…A slightly different hydrothermal synthesis process was reported by Liu et al , who successfully synthesized nail-like α-SnWO 4 nanorod arrays on WO 3 films. 58 In contrast to the hydrothermal conversion involving pre-existing nanostructured WO 3 films, this approach utilized dense WO 3 films as starting points, and the hydrothermal step simultaneously converted WO 3 to α-SnWO 4 and promoted the growth of α-SnWO 4 nanorods. The hydrothermal synthesis was performed in an aqueous solution containing SnCl·2H 2 O, NaF, and N 2 H 4 .…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…The material shows n-type conductivity, which means that it should be employed as the photoanode in PEC water splitting devices. Several studies have been reported in the last few years on α-SnWO 4 films prepared by different techniques, [10][11][12][13][14][15][16][17][18][19][20][21][22] e.g., hydrothermal synthesis, reactive magnetron sputtering, pulsed laser deposition, and chemical vapor deposition. The attractive properties of this material as a photoanode include the bandgap of 1.9 eV, which is close to ideal for use as a top absorber in a tandem configuration, and the favorably low onset potential of %0 V versus RHE.…”
Section: Introductionmentioning
confidence: 99%
“…Grain boundaries have been reported to limit charge transport, [10] and the transport properties are reported to be highly anisotropic. [18,25] Epitaxial or highly oriented films are therefore expected to have much improved charge transport, and indeed recent reports on two-dimensional α-SnWO 4 crystalline nanosheets with preferred {001} orientation demonstrated superior performance. [18][19][20] Another limitation is the modest photovoltage that can be extracted from the material, despite the fact that the band positions straddle the water reduction and oxidation potentials (which would enable a maximum quasi-Fermi level splitting of at least 1.23 V under operating conditions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above modification methods, crystal facet control is also a good modification method. , Because different crystal facets have different physical and chemical properties, some crystal facets may exhibit exceptional PEC performance. For example, the conductivity of TiO 2 in the (001) direction is roughly 60 times greater than it is in the (010) direction .…”
Section: Introductionmentioning
confidence: 99%